Study on the relationship between Global Positioning System Total Electron Content Anomalies and Earthquake Events in Thailand during Solar Cycle 24 - Chollada Pansong; Prasert Kenpankho (Earth Sciences Research Journal, 2025)
This study investigates ionospheric Total Electron Content (TEC) anomalies in relation to earthquake events in Thailand from 2007 to 2020, encompassing Solar Cycle 24. TEC data were obtained from three sources: the Global Positioning System (GPS), the International GNSS Service (IGS), and the International Reference Ionosphere (IRI), and were compared to 473 earthquakes (Mw ≥ 3.0). While earthquake magnitudes below Mw 5.0 did not exhibit a clear correlation, earthquake events of Mw 5.0 or higher reflected in moderate negative correlation coefficients for GPS TEC, IGS TEC, and IRI TEC (-0.495, -0.501, and -0.303, respectively). Furthermore, a positive correlation coefficient (0.611) was found between Mw ≥ 5.0 earthquakes and geomagnetic storms with the Kp index. However, focusing specifically on geomagnetic storms and TEC variations on the day of an earthquake, no significant relationship was detected across GPS, IGS, and IRI data. Nevertheless, further research is needed to clarify the link between seismic activity and TEC fluctuations, potentially through alternative approaches or targeted case studies. This is especially important given the limited number of earthquakes above a magnitude of 5.0 in our study area, which restricts the available sample size.
Keywords: Earthquake Detection and Analysis; Ionosphere and magnetosphere dynamics; Geomagnetism and Paleomagnetism Studies